Optimal Propagation Model for DVB-T2 System in Urban Area - Sulistyawan, Vera Noviana; Pamungkas, Damar Purba; Andrasto, Tatyantoro; Fathoni, Khoirudin; Widhira, Sepfianda Eka; Abas, Faizal Ghozali; Setiyani, Hendra Dewinta (Faculty of Engineering, Universitas Tanjungpura, 2024)
The large-scale implementation of analog switch-off for television broadcasting in Indonesia has led to blank spots in several regions. To address this issue, an optimal propagation model is needed. Proper selection and analysis of the channel model can enhance transmitter coverage, increase coverage percentage, improve energy efficiency, and boost field strength due to optimal transmit power. Previous studies have explored various DVB-T2 propagation models, notably the ITU-R P.1812-4 and Longley-Rice models, which are sophisticated and consider various environmental parameters, making them suitable for diverse broadcasting conditions. This research introduces a novel approach by specifically focusing on the urban context of Semarang City, Indonesia, to reduce blank spots by applying the ITU-R P.1812-4 and Longley-Rice propagation models. This study uniquely compares the two models to determine the most effective one for this urban area. Results indicate that the ITU-R P.1812-4 model provides a higher field strength value than the Longley-Rice model, with average field strengths of 108.3425 dBÎ¼V/m and 108.2325 dBÎ¼V/m, respectively. The difference in average field strength of 0.11 dBÎ¼V/m, despite having the same free space loss value of 100.9025 dB, indicates that one model has a slightly stronger signal. This stronger signal can improve coverage by reaching further distances and penetrating obstacles better. Additionally, a stronger signal means less power is needed to maintain the same coverage area, thus improving energy efficiency. This research not only offers empirical data specific to Semarang City but also provides insights that can guide future digital broadcasting optimizations in similar urban environments.